Sensitivity to change of the field-based Wheelchair Mobility Performance Test in wheelchair basketball - Annemarie M.H. de Witte; Fleur Sjaarda; Jochem Helleman; Monique A.M. Berger; Lucas H.V. van der Woude; Marco J.M. Hoozemans (Medical Journals Sweden, 2018)
Objective: The Wheelchair Mobility Performance (WMP) test is a reliable and valid measure to assess mobility performance in wheelchair basketball. The aim of this study was to examine the sensitivity to change of the WMP test by manipulating wheelchair configurations. Methods: Sixteen wheelchair basketball players performed the WMP test 3 times in their own wheelchair: (i) without adjustments ("control condition"); (ii) with 10 kg additional mass ("weighted condition"); and (iii) with 50% reduced tyre pressure ("tyre condition"). The outcome measure was time (s). If paired t-tests were significant (p< 0.05) and differences between conditions were larger than the standard error of measurement, the effect sizes (ES) were used to evaluate the sensitivity to change. ES values ≥0.2 were regarded as sensitive to change. Results: The overall performance times for the manipulations were significantly higher than the control condition, with mean differences of 4.40 s (weight - control, ES = 0.44) and 2.81 s (tyre - control, ES = 0.27). The overall performance time on the WMP test was judged as sensitive to change. For 8 of the 15 separate tasks on the WMP test, the tasks were judged as sensitive to change for at least one of the manipulations. Conclusion: The WMP test can detect change in mobility performance when wheelchair configurations are manipulated.